(untitled) (Homoeopathy for All, 2026)
Ocean-derived remedies represent a distinctive and conceptually significant group within homoeopathic materia medica, prepared from a variety of marine sources including organisms, minerals, and seawater. These remedies are closely associated with deep-rooted psychological patterns that reflect fundamental dimensions of human experience. They commonly express core polarities such as connection versus isolation, vulnerability versus protection and sensitivity versus withdrawal. Such contrasting tendencies offer valuable insight into subconscious conflicts, primitive survival responses and their manifestation in clinical conditions.